2007
DOI: 10.1002/bio.1003
|View full text |Cite
|
Sign up to set email alerts
|

Study on the generation mechanism of reactive oxygen species on calcium peroxide by chemiluminescence and UV‐visible spectra

Abstract: In the present work, the generation mechanism of reactive oxygen species (ROS) on calcium peroxide (CaO 2 ) was studied. A very intense chemiluminescence (CL) signal was observed when adding an aqueous solution of luminol or 2-methyl-6-(4-methoxyphenyl)-3,7-dihydroimidazo[1,2α]-pyrazin-3-one hydrochloride (MCLA) to a suspension of CaO 2 . The ROS released on CaO 2 were thought to be oxidizing agents leading to CL, and were characterized by CL, UV-visible (UV-vis) spectra and the effective scavengers of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 32 publications
(29 reference statements)
4
36
0
Order By: Relevance
“…Liang et al also reported the similar scavenger results caused by the heterogeneous catalyst happened on copper oxidate surface in the PS/copper oxidate system [50]. CP could readily redox through obtaining a single electron in the suspension of alkaline earth metal peroxides to offer Å OH [51]. Compared to MeOH, TBA was easier to react with the radicals close to the surface of CP due to its relatively low solubility.…”
Section: Identification Of Reactive Speciesmentioning
confidence: 66%
“…Liang et al also reported the similar scavenger results caused by the heterogeneous catalyst happened on copper oxidate surface in the PS/copper oxidate system [50]. CP could readily redox through obtaining a single electron in the suspension of alkaline earth metal peroxides to offer Å OH [51]. Compared to MeOH, TBA was easier to react with the radicals close to the surface of CP due to its relatively low solubility.…”
Section: Identification Of Reactive Speciesmentioning
confidence: 66%
“…Besides its stable oxidation capability, CaO 2 also possesses the capacities of bleaching, disinfection, and deodorizing. Hence, CaO 2 has been widely used in agriculture, aquiculture, and medicine (Ma et al, 2007). CaO 2 can be used to promote organic pollutant degradation in contaminated soil due to its oxidation (Ndjou'ou and Cassidy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, a few of predecessors indicates that some of the H 2 O 2 produced can rapidly react on the surface of CaO 2 , forming free radicals (hydroxyl radical and superoxide) [36]. These unstable species can immediately react and form O 2 .…”
Section: The Decomposition Behavior Of Cao 2 With Respect To O 2 and mentioning
confidence: 98%